IMPLEMENTATION OF ENVIRONMENTAL EDUCATION AND TRAINING IN TEACHING THE COURSE OF INORGANIC CHEMISTRY (World Bulletin of Social Sciences, 2021)
Inorganic chemistry, the science of chemistry. elements and the substances formed by them (with the exception of organic), the most important area of chemistry. Main tasks of modern N. kh .: the study of the structure, properties and chemical. transformations of substances, the relationship of their structure (for solids, in addition, particle size) with the properties and reactivity, the development of methods for the synthesis and purification of substances, general methods of obtaining inorganic,materials